Out-of-home day care and health. Issue 1 (January 1996) - Roberts, I
Abstract : Evidence from randomised trials indicates that out-of-home day care has important effects in domains that are integral to the health of mothers and children. The evidence that day care results in cognitive gains is compelling. These effects and the long term effects in reducing crime and violence should suffice to put the question of day care provision high on the paediatric agenda. However, some important questions remain to be answered. Evidence from a randomised trial suggests that the effect of infant day care on infectious disease morbidity is not as great as would be expected on the basis of results from observational studies. However, the trial in question had some important methodological weaknesses. No trials to date have examined the effect of day care on otitis media. Data from observational studies on the effect of day care on injury occurrence are confliciting. Finally, studies in the US point to an important effect of out-of-home day care on maternal employment. The effect of day care on maternal employment and income inequality in Britain has yet to be examined.